1979
DOI: 10.1007/bf02139137
|View full text |Cite
|
Sign up to set email alerts
|

Transition or transformation? Personal and political development of former Berkeley Free Speech Movement activists

Abstract: Former Berkeley Free Speech Movement activists' sociopolitical status, self and ideal self constructions, perceptions of parents' child-rearing practices and moral reasoning were compared with an assessment made 11 years earlier following the Berkeley Sproul Hall sit-in. Activists were found to be less politically active, more tempered in their political radicalism, more pragmatic and personally reactive in their self and ideal self conceptualizations, more critical in their perceptions of parental relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 9 publications
4
31
0
Order By: Relevance
“…The latter reason would explain why we still have rather few studies on the cultural aspects of movements except for the individual-level consequences of participation in social movements and activism, on which there is a considerable body of literature (e.g. Abramowitz & Nassi 1981, Demerath et al 1971, Fendrich 1974, 1977, Fendrich & Krauss 1978, Fendrich & Lovoy 1988, Fendrich & Tarlau 1973, Jennings 1987, Jennings & Niemi 1981, Marwell et al 1987, McAdam 1988, Nassi & Abramowitz 1979, Whalen & Flacks 1980.…”
Section: Success Failure Outcomes Consequencesmentioning
confidence: 99%
“…The latter reason would explain why we still have rather few studies on the cultural aspects of movements except for the individual-level consequences of participation in social movements and activism, on which there is a considerable body of literature (e.g. Abramowitz & Nassi 1981, Demerath et al 1971, Fendrich 1974, 1977, Fendrich & Krauss 1978, Fendrich & Lovoy 1988, Fendrich & Tarlau 1973, Jennings 1987, Jennings & Niemi 1981, Marwell et al 1987, McAdam 1988, Nassi & Abramowitz 1979, Whalen & Flacks 1980.…”
Section: Success Failure Outcomes Consequencesmentioning
confidence: 99%
“…Here too, the subjects were surveyed once again at a later stage in order to assess the impact of their involvement in the long run (Fendrich 1993;Fendrich and Lovoy 1988). Other important studies of former New Left activists were conducted by Jennings and Niemi (1981), Nassi and Abramowitz (1979;see further Abramowitz and Nassi 1981), and Whalen and Flacks (1980, 1984, 1989.…”
Section: Introductionmentioning
confidence: 99%
“…The studies that do exist on this neglected topic typically focus on what the activists do politically. Over time, however, activists gradually move away from collective involvement and movement commitment, although resisting involvement in established institutions (Nassi 1981;Demerath, Marwell, and Aiken 1971;Nassi and Abramowitz 1979;Krauss 1972;Gitlin 1987;Whittier 1995;Whalen and Flacks 1989). Over time, however, activists gradually move away from collective involvement and movement commitment, although resisting involvement in established institutions (Nassi 1981;Demerath, Marwell, and Aiken 1971;Nassi and Abramowitz 1979;Krauss 1972;Gitlin 1987;Whittier 1995;Whalen and Flacks 1989).…”
Section: The State Of Knowledge Activists At the End Of Their Movementmentioning
confidence: 99%
“…Several of them have found that former activists are concentrated in the teaching or other "helping" professions (Fendrich 1974;Maidenberg and Meyer 1970), social service, or the creative occupations (Nassi and Abramowitz 1979;Fendrich and Tarleau 1973;Nassi 1981;Fendrich 1974). Several of them have found that former activists are concentrated in the teaching or other "helping" professions (Fendrich 1974;Maidenberg and Meyer 1970), social service, or the creative occupations (Nassi and Abramowitz 1979;Fendrich and Tarleau 1973;Nassi 1981;Fendrich 1974).…”
Section: The State Of Knowledge Activists At the End Of Their Movementmentioning
confidence: 99%